2020
DOI: 10.1111/and.13494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lycopene on testicular androgenic and anti‐oxidative enzymes in cyproterone acetate‐induced male infertile Wistar strain albino rats: An in vitro study

Abstract: Incidents of male infertility are mushrooming worldwide. Oxidative stress plays a prime role for its onset. Considering this background, the study was designed to focus the direct role of lycopene on cyproterone acetate (CPA) induced testicular hypofunction in rat. Four groups have been considered including the vehicle‐treated control, lycopene‐treated control, CPA‐treated and CPA+ lycopene‐treated groups. Androgenic, antioxidant and toxicity profiles were assessed. Results focused a nonsignificant (p > .05) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Various studies have investigated the effects of lycopene on fertility in men and animals and showed promising results. They proposed that lycopene could protect sperm from OS by reducing the ROS level and increasing antioxidant enzymatic levels (Babaei, et al., 2021 ; Babaei, Moradi, et al., 2021 ; Durairajanayagam et al., 2014 ; Tripathy et al., 2020 ). They also explained that this performance of lycopene reduces sperm DNA fragmentation, LPO of the plasma membrane, and finally improves concentration, motility, viability, and morphology in the sperms of humans (Lu‐Lu & Zhi‐Gang, 2020 ; Williams et al., 2020 ) and animals (Babaei, Asadpour, et al., 2021 ; Babaei, Moradi, et al., 2021 ; Tripathy et al., 2020 ; Tvrda et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated the effects of lycopene on fertility in men and animals and showed promising results. They proposed that lycopene could protect sperm from OS by reducing the ROS level and increasing antioxidant enzymatic levels (Babaei, et al., 2021 ; Babaei, Moradi, et al., 2021 ; Durairajanayagam et al., 2014 ; Tripathy et al., 2020 ). They also explained that this performance of lycopene reduces sperm DNA fragmentation, LPO of the plasma membrane, and finally improves concentration, motility, viability, and morphology in the sperms of humans (Lu‐Lu & Zhi‐Gang, 2020 ; Williams et al., 2020 ) and animals (Babaei, Asadpour, et al., 2021 ; Babaei, Moradi, et al., 2021 ; Tripathy et al., 2020 ; Tvrda et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly showed that lipid peroxidation, total antioxidant capacity, the level of catalase, and SOD improved in varicocele-treated rats with lycopene especially at a dose of 10 mg/kg. Tripathy et al (2020) investigated the direct role of lycopene on cyproterone acetate (CPA)-induced infertility in rat. They showed antioxidant enzyme activities such as catalase, peroxidase, SOD, and GST were recovered after direct exposure of lycopene to the CPA-treated (CPA + lycopene-treated) infertile animals may be due to the potent antioxidant activity of lycopene either by rapid destruction of free radical (Tripathy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…( 2020 ) investigated the direct role of lycopene on cyproterone acetate (CPA)‐induced infertility in rat. They showed antioxidant enzyme activities such as catalase, peroxidase, SOD, and GST were recovered after direct exposure of lycopene to the CPA‐treated (CPA + lycopene‐treated) infertile animals may be due to the potent antioxidant activity of lycopene either by rapid destruction of free radical (Tripathy et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its lipophilic nature allows for its presence in various sources such as tomatoes, papayas, watermelons, apricots, pink grapefruits, and rosehips [ 10 , 57 ]. Numerous studies have demonstrated the potential effects of lycopene supplementation on seminal characteristics in humans [ 58 , 59 , 60 ], cattle [ 61 , 62 ], and rats [ 57 , 63 ]. In rams, Souza H.M. et al (2019) investigated the impact of lycopene supplementation in a Tris–egg yolk extender on various sperm parameters including sperm kinetics, plasma and acrosomal membrane integrity, intracellular ROS production, and lipid peroxidation of the plasma membrane post-freezing and thawing.…”
Section: The Current Status Of Non-enzymatic Antioxidant Utilization ...mentioning
confidence: 99%